Closed form models for dwell point locations for overhead bridge cranes. (2nd March 2009) - Hale, Trevor S.; Huq, Faizul; Blackhurst, Jennifer V.; Cutright, Ken
This research presents a methodology for determining the optimal dwell point location for an overhead bridge crane to minimise the expected response times. The problem is modelled as a planar minisum location problem with both zero dimensional (point) and two-dimensional (planar) existing demands. These demands come in three forms: from the Input/Output (I/O) location into the service area (storage move), from the service area to the I/O (retrieval move); and, across the service area (intra-service area move). The result is a non-trivial solution to where the crane should dwell when it is idle. Results of an implementation are also presented.